2019
DOI: 10.1093/geroni/igz038.037
|View full text |Cite
|
Sign up to set email alerts
|

Career Perceptions and Ideals for Clinically Focused and Academic Psychology Careers: A Mixed-Methods Study

Abstract: More psychologists who have specialty training in geriatrics are needed to meet the growing demand. However, there is a shortage of individuals in academic geropsychology, which feeds the clinical geropsychology pipeline. Barriers to recruiting trainees into jobs in academia are not well understood. The current mixed-methods study examined trainees’ perceptions of clinically-focused and academic jobs, and discrepancies between professional psychologists actual and ideal job activities. Results found that train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In higher education, job satisfaction arises from the interplay of intrinsic, extrinsic, and environmental factors. Studies like Tran and Do (2020) and Strong et al (2021) emphasize intrinsic motivators such as academic freedom and personal achievement, counterbalanced by the stress and burnout noted by Singh et al (2022). Extrinsic factors, including salary and job security, crucial in Rothacker-Peyton et al (2022), highlight remuneration and workplace safety as satisfaction determinants.…”
Section: Job Satisfaction In Academiamentioning
confidence: 99%
“…In higher education, job satisfaction arises from the interplay of intrinsic, extrinsic, and environmental factors. Studies like Tran and Do (2020) and Strong et al (2021) emphasize intrinsic motivators such as academic freedom and personal achievement, counterbalanced by the stress and burnout noted by Singh et al (2022). Extrinsic factors, including salary and job security, crucial in Rothacker-Peyton et al (2022), highlight remuneration and workplace safety as satisfaction determinants.…”
Section: Job Satisfaction In Academiamentioning
confidence: 99%
“…Thus, the current study is interested in understanding factors relevant to trainees' decisions to pursue different career paths. Previous work (Buckley, Sanders, Shih, & Hampton, 2000;Himelein & Putnam, 2001), as well as a recent study by our group (Strong et al, 2019), has highlighted that the allocation of time to various work activities (i.e., clinical, research, or teaching) varied depending on the career path chosen (i.e., primarily academic or primarily clinical position). Our findings further suggested that developing professionals' impressions of work time allocations were not fully consistent with those reported by professionals.…”
mentioning
confidence: 99%
“…Our findings further suggested that developing professionals' impressions of work time allocations were not fully consistent with those reported by professionals. Specifically, geropsychology trainees viewed academic work to be primarily focused on research and teaching, with little time allocated to clinical activities (Strong et al, 2019). Yet, participants who identified as academic geropsychologists reported spending almost 20% of their professional time in direct clinical care or supervision of clinical care.…”
mentioning
confidence: 99%